Initiative use of climate change hotspots for targeting adaptation sites in Indonesia. Issue 1 (November 2021) - Mustofa, Ikrom; Perdinan,; Pratiwi, Syafararisa Dian; Aprilia, Suvany; Tjahjono, Raden Eliasar Prabowo; Janna, Sabila Cahyaning; Wibowo, Arif; Kardono,; Wijanarka, Koko
Abstract: Designing climate change adaptation actions are considerably a challenge, as the actions should be targeted uniquely addressing climate change impacts. One of the challenges is to determine climate change adaptation sites. The complexity raises considering climate change impact a wide range of economic sectors, which require a lot of resources to conduct a comprehensive climate change assessments. This study proposes the use of climate change hotspots as an initiative to firstly consider the potential targeted sites. The target of global efforts to maintain air temperature under 2°C was employed as a clue to prioritize areas that air temperature is increasing beyond the thresholds to which can affect human activities. This study employed spatial and threshold analysis to develop climate change hotspots of projected temperature change for 2021-2050 over Indonesia. The thresholds were defined by considering the effects of base temperature of 32 °C, 35 °C, and 38 °C on agriculture, environment, and human health in combination with elevated temperature from 0.75 to 2 °C. The initiative method was applied to the baseline and projected air temperature obtained from higher resolution of climate model outputs simulated under representative carbon pathway scenario of 4.5 (RCP 4.5 and 8.5) as a case study. The maps of climate change hotspots provide the potential targeted areas for climate change adaptation actions. Referring to the target of suppressing global temperatures below 2°C, we identified the distribution of climate change hotspots in Indonesia with a scenario of increasing temperature of 2°C from baseline conditions so that future air temperatures will be more than 35°C. The maps can also be combined with the other maps related to climate change analyses, which are available in Indonesia such as SIDIK to refine the priority areas and/or more general geographic information such as city location. As an example, the overlay of climate change hotspots and city location can provide early anticipation on which city will experience urban heat island. The development of climate change hotspots nationally is also expected to initiate climate change services that can be provided to the end users to ease them in defining suitable actions to adapt to the impacts of climate change.